Maximum Bony Gape in Primates. Issue 2 (9th November 2018) - Fricano, Ellen E. I.; Perry, Jonathan M. G.
ABSTRACT: Maximum jaw gape has important functional implications for behavior and feeding habits in primates. It has been suggested that gape is correlated to canine height and ingested food size. Extending these correlations to the fossil record would provide insights about the diets and/or social behavior of extinct primates. However, this can be problematic due to uncertainty about size and location of musculature, and it depends on reliability and repeatability of maximum gape estimation using only skeletal elements. In this study, maximum bony gape (MBG) was estimated using reliable landmarks and repeatable methods. The cranium was fixed in position and then the mandible was rotated and translated to the point immediately prior to loss of condyle‐glenoid contact. Then it was photographed in a steady position using an adjustable wooden frame. This protocol allowed for photographs and linear measurements to be obtained for many museum specimens in a short time. The sample included 203 individuals, representing 42 species of primates. When scaled for body size, linear MBG correlates with maximum anesthetized gape (Hylander: Am J Phys Anthropol 150 (2013) 247–259), ingested food size (Perry and Hartstone‐Rose: Am J Phys Anthropol 142 (2010) 625–635), and canine length but not condylar height. Anat Rec, 302:215–225, 2019. © 2018 Wiley Periodicals, Inc.